2015
DOI: 10.1159/000381714
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Interleukin-6</i></b> CpG Methylation and Body Weight Correlate Differently in Type 2 Diabetes Patients Compared to Obese and Lean Controls

Abstract: Background/Aims: Diabetes mellitus type 2 (DMT2) is accompanied by systemic low-grade inflammation with elevated levels of interleukin-6 (IL-6), which is encoded by a gene (IL-6) previously shown to be regulated by DNA methylation. We investigated seven CpG sites in IL-6 in individuals with DMT2, obese individuals and lean controls. Further, the DMT2 group received the glucagon-like peptide 1 agonist liraglutide. Methods: Blood samples were taken at the beginning of the study and after 4 months. The DNA methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Prospective studies are required to elucidate the temporal nature of this association. However, given the implication of IL-6 in the pathogenesis of CHD and the inverse correlation of IL-6 promoter methylation with CHD risk factors, 25 , 37 our results suggest that demethylation of the IL-6 promoter may contribute to the risk of developing CHD. Secondly, the functional effect of the IL-6 promoter hypomethylation was not further investigated in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…Prospective studies are required to elucidate the temporal nature of this association. However, given the implication of IL-6 in the pathogenesis of CHD and the inverse correlation of IL-6 promoter methylation with CHD risk factors, 25 , 37 our results suggest that demethylation of the IL-6 promoter may contribute to the risk of developing CHD. Secondly, the functional effect of the IL-6 promoter hypomethylation was not further investigated in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…The implication of IL-6 in the pathogenesis of CHD and the inverse correlation of IL-6 promoter methylation with CHD risk factors have been demonstrated [55]. Previous studies have been reported that hypomethylation of IL-6 promoter was associated with the pathogenesis of systemic lupus erythematous, rheumatoid arthritis, chronic periodontitis and CHD [56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Higher gene expression of IL-6 protein has been associated with various diseases including cancer, rheumatoid arthritis, insulin resistance and diabetes [51,79,80]. Promoter methylation is one of the regulation mechanisms of IL-6 gene expression and is correlated to body weight [51,81]. Furthermore, studies revealed an association between elevated mRNA levels of interleukin 6 and a Promoter demethylation [82,83].…”
Section: Discussionmentioning
confidence: 99%